Memerangi Kejahatan Kehutanan dan Mendorong Prinsip Kehati-hatian Perbankan untuk Mewujudkan Pengelolaan Hutan yang Berkelanjutan Pendekatan Anti Pencucian Uang - Setiono, Bambang; Husein, Yunus (Indonesian Journal of International Law, 2021)
If the illegal logging is just a criminal whose involve the poor society which their life depend to the forest, truck driver or forest guards whose underpaid, that criminal would not be difficult to stop. With the involvement of support from the illegal logging funders, which usually called cukong, illegal logging industry and government employees, the illegal logging has become a complex problem, not only in Indonesia, but also for the international forest community. The forestry law enforcement approach which now is running failed to capture the mastermind of illegal logging. But, the money laundering law enforcement approach which with the approach in “follow the money” may be the option to face the actors in illegal logging. This approach requires the bank and the other financial service providers for more active and careful in run the financial transaction whose related to their customers. Bank customers may be the funders of illegal logging, wood industry, law enforcement instrument and government instrument. Overall, the use of anti-money laundering regime effectively will give the opportunies to encourage the banking precautionary principles and the forest management, and to reduce the forest criminal.